Notch signaling sculpts the stem cell niche - Zamfirescu, Ana-Maria; Yatsenko, Andriy S.; Shcherbata, Halyna R. (Frontiers in Cell and Developmental Biology, 2022)
Adult stem cells depend on their niches for regulatory signaling that controls their maintenance, division and their progeny differentiation. While communication between various types of stem cells and their niches is becoming clearer, the process of stem cell niche establishment is still not very well understood. Notch signaling is an evolutionarily conserved pathway is crucial in fate acquisition and spatiotemporal patterning. While the core logic behind its activity is fairly simple and requires direct cell-cell interaction, it reaches an astonishing complexity and versatility by combining its different modes of action. Subtleties such as equivalency between communicating cells, their physical distance, receptor and ligand processing and endocytosis can have an effect on the way the events unfold and this review explores some important general mechanisms of action, later on focusing on its involvement in stem cell niche formation. Firstly, looking at invertebrates, we will examine how Notch signaling induces the formation of the germline stem cell niche in Drosophila. Intriguingly, a double security mechanisms of Notch signaling activation coordinated by the soma or the germline control both steps to ensure the robustness of niche assembly. Secondly, in the vast domains of mammalian cellular signaling there is an emerging picture of Notch being an active player in a variety of tissues in health and disease. Notch involvement has been shown in stem cell niche establishment in multiple organs, including brain, muscle and intestine, where the stem cell niches are essential for the maintenance of adult stem cells. But adult stem cells are not the only one looking for a home. Cancer stem cells are utilizing Notch signaling at specific stages to gain an advantage over endogenous tissue and overpower it, at the same time acquiring migratory and invasive abilities to claim new tissues (e.g. bone) as their territory. Moreover, in vitro models such as organoids reveal similar Notch employment when it comes to the developing stem cell niches. Therefore, a better understanding of the processes regulating stem cell niche assembly is key for the fields of stem cell biology and regenerative medicine.